Microscopía electrónica de barrido del epitelio digestivo del grillo (Gryllus sp.) - Malavasi, Jollyanna (1981)
An ultrastructural description of the pharynx, esophagus, crop, gizzard, gastric caeca, stomach, hind intestine and rectal sac of Gryllus sp. was performed under scanning electronic microscopy.Both the pharynx and the esophagus present an epithelium formed by overlapping sheets containing several thorn-like projections. The crop shows transversal and longitudinal creases and is covered by the same type of overlapping sheets found on the pharynx and the esophagus.The most complex fine structure was observed in the gizzard. This part shows a very irregular epithelium where four different sub units are distinguished, which together conform the characteristic units of this species.The fine structure of the epithelium, of the stomach and gastric caeca is very homogeneous, downy, velvet-like, due to the millions of fine hairs that totally cover this zone of the tract.The intestinal digestive epithelium is very smooth and at the large intestine level it shows some conic prominences.